Charity and redistributive taxation in a unionized economy - Giacomo Corneo (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
European economies are characterized by unionized labor markets and a pronounced governmental redistribution of income. This paper studies a model where those two features are combined with the possibility for individuals to make charitable contributions to the poor. The model exhibits equilibrium unemployment that increases with the degree of altruism. It is shown that a more progressive income tax can both reduce the unemployment rate and improve the public budget. These results are driven by charity increasing wage pressure and the altruistic rich failing to internalize the effect of their donations on the wage setting behavior of the unions.
Keywords: J50; H24; 330; Equilibrium Unemployment; Income Tax; Charity; Trade Unions